Gold rush girl - Avi, 1937- (Somerville, MA : Candlewick Press, 2020)
"Victoria Blaisdell longs for independence and adventure, and she yearns to accompany her father as he sails west in search of real gold! But it is 1848, and Tory isn't even allowed to go to school, much less travel all the way from Rhode Island to California. Determined to take control of her own destiny, Tory stows away on the ship. Though San Francisco is frenzied and full of wild and dangerous men, Tory finds freedom and friendship there. Until one day, when Father is in the gold fields, her younger brother, Jacob, is kidnapped. And so Tory is spurred on a treacherous search for him in Rotten Row, a part of San Francisco Bay crowded with hundreds of abandoned ships. Beloved storyteller Avi is at the top of his form as he ushers us back to an extraordinary time of hope and risk, brought to life by a heroine readers will cheer for. Spot-on details and high suspense make this a vivid, absorbing historical adventure"--